Financing of the SMEs in the European Union Through Credit Institutions - Valentina Diana Ignatescu (CES Working Papers, 2010)
It is widely acknowledge that financial constraints are the most visible problems of the SMEs. So through this paper we propose to analyze the main sources of financing that SMEs use to conducttheir business. And, from these sources, we should focus on the ways of financing offered by credit institutions. Thus, we will identify the main sources of financing available to SMEs and offered by creditinstitutions. Banks are increasingly seeking to become facilitators and partners with their SME clients. In other words, they try to offer a broader range of products, better service quality and better prices. Through this paper we will see if the bank offers are truly advantageous for SMEs.
Keywords: 330; internal funds; bank loans; trade loans; European Investment Bank; subordinated loans